Recessive truncating IGHMBP2 mutations presenting as axonal sensorimotor neuropathy. (3rd February 2015) - Schottmann, Gudrun; Jungbluth, Heinz; Schara, Ulrike; Knierim, Ellen; Morales Gonzalez, Susanne; Gill, Esther; Seifert, Franziska; Norwood, Fiona; Deshpande, Charu; von Au, Katja; Schuelke, Markus; Senderek, Jan
Abstract : Objective: To identify the cause of sensorimotor neuropathy in a cohort of patients with genetically unsolved neuropathies (57 families with a total of 74 members) in whom hitherto known disease genes had been excluded. Methods: We used autozygosity mapping or haplotype analysis to delineate potential disease loci in informative families. For mutation detection, we used either whole-exome sequencing or Sanger sequencing of positional candidates. Subsequently, a larger cohort was specifically screened for IGHMBP2 mutations. The pathogenicity of a splice-site mutation was verified in cultured patient skin fibroblasts on the messenger RNA level and by Western blot. Results: We report on 5 patients with neuropathy from 3 families who carried truncating mutations in IGHMBP2 . Contrary to the "classic" phenotype, they did not manifest with respiratory distress, but with progressive sensorimotor neuropathy. Only one patient required nocturnal mask ventilation, while 4 others maintained normal respiratory function by the age of 14, 18, 22, and 37 years. Three patients were still able to walk independently. All patients had a predominantly axonal sensorimotor neuropathy with subsequent muscle atrophy, but without obvious sensory symptoms. Two patients had signs of autonomic neuropathy. Conclusions: Mutations in IGHMBP2 should be considered in the molecular genetic workup of patients with hereditary sensorimotor neuropathies, even in the absence of respiratory symptoms.